THE RELEVANCE OF SCREENING FOR PHARMACEUTICAL AND MEDICAL PREVENTION OF HIV INFECTION - Петров, Андрей Георгиевич; Хорошилова, Ольга Владимировна; Филимонов, Сергей Николаевич; Семенихин, Виктор Андреевич; Черных, Наталья Степановна (Medicine in Kuzbass, 2023)
The review examines the relevance of screening for pharmaceutical and medical prevention of HIV infection. Infection caused by the human immunodeficiency virus (HIV) is one of the most severe non-epidemic and socially caused infectious diseases worldwide. The review is devoted to the importance of screening for pharmaceutical and medical prevention of HIV infection, the results of the analysis of morbidity at the Russian and regional levels are presented. The prospects of introducing screening into the activities of medical organizations for the development of HIV prevention programs are shown.
Keywords: morbidity; HIV infection; acquired immune deficiency syndrome; population; screening